1980
DOI: 10.1007/bf02265219
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue of metal matrix composites

Abstract: One unidirectional and two laminated 6061-0 A~e-B composite plates were tested under various cyclic loading conditions. Three types of material response to cyclic loading were identified; No evidence of damage at relatively low cyclic loads, damage accumulation caused primarily by growth of long matrix cracks parallel to the fibers in off-axis layers at higher loads, and sudden localized failure of the fibers. Quantitative analysis of the results shows that the extent of internal damage, demonstrated by a redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 14 publications
0
15
1
Order By: Relevance
“…i -1 --The Hi is the stress distribution factor in (2), and L, M are the overall in-plane stiffness and compliance of the laminated plate; all are (3 X 3) matrices.…”
Section: Vectorsmentioning
confidence: 99%
“…i -1 --The Hi is the stress distribution factor in (2), and L, M are the overall in-plane stiffness and compliance of the laminated plate; all are (3 X 3) matrices.…”
Section: Vectorsmentioning
confidence: 99%
“…Figure 1 shows various examples of these cracks in a (0/90/±45) laminate, which were constructed S from observations of actual crack systems described in [1,[3][4][5]. The right part of this figure, section A-A', shows an in-plane view of a crack in the 900 ply.…”
Section: Tedwicatlmentioning
confidence: 99%
“…Even so, local plastic straining can be permitted in the composite during the first few load cycles, provided that the composite "shakes downtt during these few cycles. The shakedown stress is reached if the matrix cyclically hardens to a yield stress, Y, such that, subsequently, only elastic deformation occurs under load cycles [2]. Previous tests have shown that the matrix fatigue limit coincides with the stable cyclic yield stress for annealed aluminum [11,12] and steels 1121.…”
Section: Matrix Dominated Damagementioning
confidence: 99%
“…Dvorak and Tarn suggested that the shakedown stress was related to laminate S-N type fatigue failure. Since 1979 Dvorak and Johnson [2,3,10], have examined theoretically and experimentally both unidirectional and laminated 6061-0 B/A1 composites. They found that the shakedown stress was related to the onset of fatigue damage in the composite's matrix material but not necessarily to laminate failure.…”
Section: Matrix Dominated Damagementioning
confidence: 99%
See 1 more Smart Citation